QUALITY ASSURANCE VARIABLES, INTEGRATION OF ICT TOOL AND SECONDARY SCHOOL GOAL ATTAINMENT IN YAKURR L.G.A, CROSS RIVER STATE (Journal of Association of Educational Management and Policy Practitioners, 2025)
This study investigated quality assurance variables, integration of ICT tools and secondary school goal attainment. Two research questions and hypotheses were formulated to guide and direct the study. The expostfacto research design was adopted for the study. The population of the study comprised all the 427 teachers in Yakurr secondary school. The sample for the study comprised two hundred and eighty (280) teachers drawn from the (23) secondary schools. The instruments used for data collection was a structured questionnaire titled "Quality Assurance variables, integration of ICT and secondary school Questionnaire (QAVIISQ)", Data collected were analyzed using Pearson Product Moment Correlation statistics at, 0.05 level of significance. The result of the study revealed that provision of school facilities and supervision of instructional delivery significantly relate with secondary school goal attainment. Based on this result, it was recommended that adequate facilities such as spacious classrooms with adequate functional seats, internet facilities that would enable students use e-library resources all the time, and functional laboratories, etc. should be provided in the school, adequate modality for supervising what teachers do in the classroom should be put in place.